Efficiency of Application of Hirudotherapy to Have Been Having Coronaviral Infection - Fattakhov, Nusratullo Khamidullaevich; Tilyakhodzhaeva, Gulbahor Batyrovna; Abdulkhakimov, Arsen Renatovich (RA Journal of Applied Research, 2021)
The article provides information on medical leeches that are suitable for medical treatment. Also, the authors studied the effect of hirudin on the human body in different age, the number of leeches and sessions required to obtain a therapeutic effect.